(When) Is Science Reporting Ethical? The Case for Recognizing Shared Epistemic Responsibility in Science Journalism - Figdor, Carrie (Frontiers in Communication, 2017)
Internal mechanisms that uphold the reliability of published scientific results have failed across many sciences, including some that are major sources of science news. Traditional methods for reporting science in the mass media do not effectively compensate for this unreliability. I argue for a new conceptual framework in which science journalists and scientists form a complex knowledge community, with science news as the interdisciplinary product. This approach motivates forms of collaboration and training that can improve the epistemic reliability of science news.